Pencegahan Covid-19 Melalui Promosi Kesehatan di Wilayah Kerja Puskesmas Pemurus Dalam Kota Banjarmasin - Damaika Ayunky Nastiti Istiqomah; M. Bahrul Ilmi; Suryani Syahril; Noor Bayah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Diseases originating from the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) or better known as Covid-19 are very easily transmitted through close contact and droplets from sneezing or coughing fluids from those closest to them. The high rate of spread of the Covid-19 disease in Indonesia is one of the health problems that the public should be aware of. The accumulated data Covid-19 cases of Indonesia to date has reached 4,516,480 positive cases, 144,554 deaths, and 4,183,027 recovered cases. People living in the Pemurus Dalam area in the city of Banjarmasin are the intended targets for this Covid-19 prevention activity. By using the field observation method and direct socialization, the results obtained in the form of data positive cases of Covid-19 in the work area of the Puskesmas Pemurus Dalam from 2020 to 2022 and the behavior of people that are less aware of the dangers of the Covid-19 virus, thus ignoring health protocols and low vaccination rates in Banjarmasin. The factors causing the main problem of increasing positive cases of Covid-19 in the work area of the Puskesmas Pemurus Dalam include the lack of awareness of humans themselves, methods that have not been maximized, the environment is not supportive and limited facilities. The conclusion of the socialization/counseling activities in the context of health promotion held with the Puskesmas Pemurus Dalam will change the public's perception so that they will comply with the applicable health protocols and carry out vaccinations to maintain the body's immune system